Rod Photoresponse Kinetics Limit Temporal Contrast Sensitivity in Mesopic Vision - Umino, Yumiko (J Neurosci, 2019)
The mammalian visual system operates over an extended range of ambient light levels by switching between rod and cone photoreceptors. Rod-driven vision is sluggish, highly sensitive, and operates in dim or scotopic lights, whereas cone-driven vision is brisk, less sensitive, and operates in bright or photopic lights. At intermediate or mesopic lights, vision transitions seamlessly from rod-driven to cone-driven, despite the profound differences in rod and cone response dynamics. The neural mechanisms underlying such a smooth handoff are not understood. Using an operant behavior assay, electrophysiological recordings, and mathematical modeling we examined the neural underpinnings of the mesopic visual transition in mice of either sex. We found that rods, but not cones, drive visual sensitivity to temporal light variations over much of the mesopic range. Surprisingly, speeding up rod photoresponse recovery kinetics in transgenic mice improved visual sensitivity to slow temporal variations, in the range where perceptual sensitivity is governed by Weber's law of sensation. In contrast, physiological processes acting downstream from phototransduction limit sensitivity to high frequencies and temporal resolution. We traced the paradoxical control of visual temporal sensitivity to rod photoresponses themselves. A scenario emerges where perceptual sensitivity is limited by: (1) the kinetics of neural processes acting downstream from phototransduction in scotopic lights, (2) rod response kinetics in mesopic lights, and (3) cone response kinetics as light levels rise into the photopic range. SIGNIFICANCE STATEMENT Our ability to detect flickering lights is constrained by the dynamics of the slowest step in the visual pathway. Cone photoresponse kinetics limit visual temporal sensitivity in bright (photopic) lights, whereas mechanisms in the inner retina limit sensitivity in dim (scotopic) lights. The neural mechanisms underlying the transition between scotopic and photopic vision in mesopic lights, when both rods are cones are active, are unknown. This study provides a missing link in this mechanism by establishing that rod photoresponse kinetics limit temporal sensitivity during the mesopic transition. Surprisingly, this range is where Weber's Law of Sensation governs temporal contrast sensitivity in mouse. Our results will help guide future studies of complex and dynamic interactions between rod–cone signals in the mesopic retina.